1998
DOI: 10.1063/1.367126
|View full text |Cite
|
Sign up to set email alerts
|

Interface acoustic modes of twisted Si(001) wafers

Abstract: Interface acoustic waves at the (001) boundary of twisted single-crystal silicon wafers are studied using analytical and numerical techniques. A secular equation of the problem in an explicit form is derived for the propagation directions along the twist-angle bisectrix and a complete numerical solution is calculated for arbitrary propagation. A new mode of leaky-wave type is predicted. This leaky mode has a low propagation loss and distinct near-interface localization at small twist angles. The leaky wave is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
2

Year Published

2003
2003
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 6 publications
0
23
2
Order By: Relevance
“…Moreover this wave, of the IAW1 type, satisfies these requirements only within a limited range of misorientation angle, approximatively 16.7 o < θ < 73.6 o . This situation is in sharp contrast with the case of silicon/silicon wafers in linear anisotropic elasticity (Mozhaev et al, 1998) where the IAW1 was found to exist for all θ. Figure 2 depicts the variations of the relevant root to the secular equation, scaled as √ X = ρv 2 , with θ (thick curve).…”
Section: Mooney-rivlin Materials In Tri-axial Straincontrasting
confidence: 44%
See 4 more Smart Citations
“…Moreover this wave, of the IAW1 type, satisfies these requirements only within a limited range of misorientation angle, approximatively 16.7 o < θ < 73.6 o . This situation is in sharp contrast with the case of silicon/silicon wafers in linear anisotropic elasticity (Mozhaev et al, 1998) where the IAW1 was found to exist for all θ. Figure 2 depicts the variations of the relevant root to the secular equation, scaled as √ X = ρv 2 , with θ (thick curve).…”
Section: Mooney-rivlin Materials In Tri-axial Straincontrasting
confidence: 44%
“…In effect, and as displayed by Mozhaev et al (1998) in the linear anisotropic elasticity case, either one displacement component and two tractions are zero at the interface, or vice-versa. More specifically, and these details were not noted by Mozhaev et al (1998), ξ(0) must be of one of the two following forms. Either…”
Section: Incremental Equations Of Motion and Effective Boundary Condimentioning
confidence: 99%
See 3 more Smart Citations